Desymmetrization of disubstituted aromatic crown ethers via intramolecular Cannizzaro reactions. (25th October 2019) - Rouser, Mason A.; Gibson, Harry W.
Abstract : Ba ++ templated Cannizzaro reactions convert symmetrical aromatic crown ether dialdehydes of various types [dibenzo and bis( meta -phenylene)] and sizes (20–32 atom rings) to acid–alcohol functionalized crown ethers in 70–98% yields. Abstract : We report a high-yielding metal templated Cannizzaro reaction for converting symmetrical aromatic crown ether dialdehydes of various types [dibenzo and bis( meta -phenylene)] and sizes (20–32 atom rings) to acid–alcohol functionalized crown ethers in 70–98% yields.